Online Misogyny and the Law: Are Human Rights Protected on the Net? - Pérez de la Fuente, Oscar (The Age of Human Rights Journal, 2023)
This paper opens by analysing the complexity of misogyny, sexism, and toxic masculinity. It then examines online misogyny, dissecting the many acts and behaviours that comprise this kind of digital discrimination. It considers the Gamergate scandal and demonstrates how the video game industry reinforces gender stereotypes. It closes with an analysis of efficiency and limits of legislative systems for combatting online sexism.